HOW READY ARE ISLAMIC EDUCATION TEACHERS IN INDONESIA TO UTILIZE ARTIFICIAL INTELLIGENCE FOR TEACHING - Miftahul Fikri; Oban Sobandi; Yuni Purnama Sari; Dwi Fikry Al-Ghifary (JURNAL EDUSCIENCE, 2026)
Purpose – There is limited empirical evidence about the readiness of Islamic education teachers to use Artificial Intelligence (AI) in teaching, especially at a national level in developing Muslim-majority countries. This study examines how ready Indonesian Islamic education teachers are to adopt AI in the classroom. It also identifies how their readiness levels vary across regions.Methodology – This study used a quantitative, cross-sectional survey design. Data came from 11,393 Islamic education teachers in 31 of Indonesia's 38 provinces. The data were analyzed with descriptive statistics to show readiness levels and inferential statistics to check the robustness of the findings.Findings – Most Islamic education teachers are positively ready to use AI. Of these, 32.6% (3,711 teachers) are very ready, 37.7% (4,294 teachers) are ready, 22.4% (2,557 teachers) are moderately ready, 4.9% (553 teachers) are not ready, and 2.4% (278 teachers) are very unready. Overall, Indonesian Islamic education teachers are generally prepared for AI integration, although some differences in readiness remain.Contribution – This study gives large-scale empirical evidence on AI readiness among Islamic education teachers. It fills a major gap in Islamic education and educational technology research. The findings support data-driven policies and professional development programs. These can strengthen the use of AI in Islamic education, while keeping pedagogical and ethical considerations in view.